PENGGUNAAN ETNOMATEMATIKA SUKU MADURA UNTUK MENGANTISIPASI HAMBATAN BELAJAR ARITMATIKA SOSIAL SISWA SEKOLAH MENENGAH PERTAMA - Astuty Saroh; Sugiatno Sugiatno; Romal Ijuddin (Universitas Tanjungpura, 2021)
AbstractThis research aimed to determine how to overcome the barriers of learning students in social arithmetic materials using Madura ethnomathematics in grade VIII B Islamic Junior High School Ashabul Kahfi Pontianak. The form of research used in this study is case study research. This study's data source is grade VIII B students of SMP Islam Ashabul Kahfi Pontianak, and the data were the initial and final test answer sheets and the results of interviews.. The results showed that Madurese ethnomathematics could overcome the barriers of student learning. Before using the ethnomathematics Madura tribe, students experienced errors in the concept of summation arranged downwards, errors in the concept of subtraction arranged downwards on numbers that have many zero digits, and errors in the concept of division, and errors calculating values in performing calculated operations. After using the ethnomathematics, the Madura tribe students can already operate using the way of counting done by traders, can already work on the problem of using the way of counting done by traders, and can already work on the problem by obtaining the correct value settlement. Although there is still students who still experience a slight error caused by the student's disability, all students cannot work using the correct steps.Keywords: Ethnomatematics, Learning Obstacles, Madura Tribe, Social Arithmetic